STRATEGI PEMBELaJARAN INKUIRI MELALUI MINI LAB SAINS DALAM PENGEMBANGAN KETERAMPILAN ABAD KE-21 - Rofiyarti, Fitri (MOTORIC, 2025)
In a global era marked by the rapid development of technology and information, 21st-century skills such as critical thinking, analytical, creative, communication, and collaboration are very important for students. This article discusses the role of the science mini lab strategy combined with the inquiry-based learning (IBL) approach as an innovative learning strategy in developing these skills. Through hands-on methods, inquiry-based learning, and independent exploration, science mini labs encourage students to actively ask questions, investigate, design experiments, and draw conclusions based on evidence. This approach has been shown to increase active participation, high-level thinking skills, and strengthen teamwork and effective communication. Through a literature review, this article describes various forms of mini lab implementation, from portable kits to virtual laboratories, as well as case studies of their use in schools. The results of various studies show that the integration of IBL in mini labs can enrich the learning experience, improve learning outcomes, and prepare students to face real-world challenges. Thus, the implementation of inquiry-based science mini labs is a strategic step in presenting contextual and empowering education.